Use of Teduglutide in Children With Intestinal Failure: A Systematic Review - Gigola, Francesca; Cianci, Maria Chiara; Cirocchi, Roberto; Ranucci, Maria Chiara; Del Riccio, Marco; Coletta, Riccardo; Morabito, Antonino (Frontiers in Nutrition, 2022)
Background and objectives Short-bowel syndrome (SBS) results from the loss of a significant portion of the small intestine leading to a state of malabsorption. After an intestinal loss, there is a process of adaptation involving the Glucagon-Like Peptide-2 (GLP-2), an enteroendocrine peptide associated with adaptive responses to resection and involved in nutrient absorption. Teduglutide is a recombinant analogue of GLP-2 approved in 2016 to treat selected short bowel syndrome in pediatric patients dependent on parenteral support. The present systematic review aims to evaluate the efficacy of Teduglutide in pediatric patients with SBS in reducing the need for parenteral nutrition (PN). Material and methods We did a literature search on MEDLINE and Embase until November 2021. We included articles that involved using Teduglutide in the SBS paediatric population to define its efficacy in reducing the need for PN. The search string used was “(GLP-2 OR GLP2 OR glucagon-like peptide 2 OR teduglutide AND child*”. Results Fourteen studies completely fulfilled the inclusion criteria. Two hundred twenty-three patients were treated with Teduglutide, and the median duration of treatment was 45 weeks (IQR: 36 weeks – 52.5 weeks). 68.2% of patients was treated with 0.05 mg/Kg/d of subcutaneous Teduglutide, 17% received 0.025 mg/Kg/d and 3.6% received either 0.125 mg/Kg/d or 0.20 mg/Kg/d. A total of 36 patients achieved EA after a median of 24 weeks of treatment (IQR: 24 weeks – 48 weeks) and 67% of patients showed a reduction in PN needs in terms of volume, calories, or hours per day. Eleven studies reported complications: gastrointestinal were the most common, with 89 cases reported in treated patients and 11 in non-treated patients. Conclusions Teduglutide appears safe and effective in reducing PN requirements and improving EA in the pediatric population. However, more studies are needed to understand its efficacy in the long term and after discontinuation and possible complications.